2017
DOI: 10.1002/pro.3107
|View full text |Cite
|
Sign up to set email alerts
|

Functional similarities between the dictyostelium protein AprA and the human protein dipeptidyl‐peptidase IV

Abstract: Autocrine proliferation repressor protein A (AprA) is a protein secreted by Dictyostelium discoideum cells. Although there is very little sequence similarity between AprA and any human protein, AprA has a predicted structural similarity to the human protein dipeptidyl peptidase IV (DPPIV). AprA is a chemorepellent for Dictyostelium cells, and DPPIV is a chemorepellent for neutrophils. This led us to investigate if AprA and DPPIV have additional functional similarities. We find that like AprA, DPPIV is a chemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Because there exist chemorepellents in higher eukaryotes (Herlihy et al. , 2013a, 2015, 2017; de Oliveira et al. , 2016; Nourshargh et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there exist chemorepellents in higher eukaryotes (Herlihy et al. , 2013a, 2015, 2017; de Oliveira et al. , 2016; Nourshargh et al.…”
Section: Discussionmentioning
confidence: 99%
“…An orthologue of AprA, dipeptidyl peptidase IV (DPPIV), acts as a chemorepellent for neutrophils (Herlihy et al. , 2013a, 2015, 2017; White et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The chemorepellent AprA increased the directness of Dictyostelium cells, while DPPIV and the PAR2 agonists induced chemorepulsion without increasing directness. This suggests a difference in the chemorepulsion mechanisms used by AprA compared to the DPPIV and PAR2 agonists.…”
Section: Discussionmentioning
confidence: 94%
“…Comparatively, much less is known about the mechanisms used by cells to move away from chemorepellents . Based on initial studies on a Dictyostelium chemorepellent, we found that the human extracellular protein dipeptidyl peptidase IV (DPPIV) is a chemorepellent for human and mouse neutrophils . Since chemoattractants activate cell surface receptors, an intriguing possibility is that a neutrophil chemorepellent such as DPPIV may also activate a neutrophil cell‐surface receptor.…”
Section: Introductionmentioning
confidence: 99%
“…A tertiary structure of AprA predicted by I-TASSER (Roy et al, 2010, Zhang, 2008, suggested that the AprA structure might have similarity to human dipeptidyl peptidase IV (DPPIV) (Hiramatsu et al, 2003). Both AprA and DPPIV are glycoproteins, have protease activity, and bind fibronectin (Herlihy et al, 2017). DPPIV is present in plasma and other extracellular fluids (Abbott et al, 1994, Cordero et al, 2009.…”
Section: Development Of Potential Therapeutics Based On Dictyosteliummentioning
confidence: 99%